Managing Periodontitis in Type 1 Diabetic Patients Improves Glycemic Control: A Case Report - Edmund Julian Ofilada (Journal of the ASEAN Federation of Endocrine Societies, 2016)
This case report describes the long-term follow-up of a 22-year-old, female patient with type 1 diabetes managed by conservative oral care and glycemic control measures. She is on a twice a day insulin regimen. Tooth numbers 13 and 37 had pockets less than 6 mm while all remaining teeth had greater than 6 mm. Periodontal management consisted of root planing combined with instructions on diabetes self-management skills at home. Nine weeks after the first sextant was treated, Pocket depth measurements in 93 (81.6%) out of 114 sites and bleeding on probing (BOP) scores in 11 (57.9%) out of 19 teeth decreased. There was a 50% reduction in the C reactive Protein and a 46.7% decrease in the fructosamine assay levels. Initial glycohemoglobin level of 8.3% decreased substantially to 7.1%. The goal of the dentist is no longer just the improvement of oral health but ultimately the overall health of the patient and the physician’s goal is to include oral health in the promotion of overall health.